Orchids of Perlis: new records and distribution - Yong, Wendy Sze Yee; Go, Rusea; Tang, Cher Hing; Abdullah, Janna Ong; Osman, Kassim (Universiti Putra Malaysia Press, 2005)
An intensive study on orchid diversity was conducted in Perlis especially within the Perlis State Park during the period 2003 - 2004. During the numerous field trips and studies, a total of 1,783 orchid specimens where collected from the 12 hills (11 limestone hills and one partly granite stone mountain). These samples were identified and differentiated into 119 taxa in 50 genera which are represented by 4 subfamilies. Ninety were identified to species level and the remaining 29 were only identified to genus level as the specimens were incomplete, because of lack of flowers. From these numbers, 62 species in 20 genera are new records for Perlis and 9 species and one genus, Panisea, are new records for Malaysia. The diversity of orchids in Perlis is characteristically closely related to Thailand’s orchid flora, which is Indo- Malayan Floristic Region or Thailand - Burmese Floristic Region as compared to the other parts of Malaya which is Malayan Floristic Region. This can be to the climatic conditions (northern dry - monsoon), geographical location (bordering Peninsular Thailand) and the limestone habitat which is known to haboura high rate of species endemism. As much as 90% of these new records of orchids were collected from near the Malaysian-Thailand border and from Gunung Perlis, the highest peak in Perlis (733m).